The retroflex r of Brazilian Portuguese: theories of origin and a case study of language attitudes in Minas Gerais - Rennicke, Iiris (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
Some scholars have linked the emergence of retroflex rhotics in Brazilian Portuguese to language contact with indigenous peoples or the neutralization of posteriorized coda liquids. In this article arguments are presented in favour of an independent phonetic change, linking BP to the variation in rhotics found in other languages. In addition, the results of an original language attitude study conducted in the state of Minas Gerais are presented and analysed. They show a social and geographical prejudice related to the speakers using retroflex rhotics, but also partially present a recurring result in language attitude studies: prestige accents score well in dimensions such as competence and status, and non-prestige accents score well in solidarity.